Assessment of Qol among COVID-19 patients in South India: A tertiary care center study: An original research - Sreedevi Janapareddi; Kiran S Shankar; Mansi Mendiratta; Neha Chauhan; Sachin Kumar Jadhav; Divya Jahagirdar (Wolters Kluwer Medknow Publications, 2023)
Introduction: The COVID-19 epidemic has brought about an unparalleled health disaster and fundamentally altered people's livelihoods. We intended to examine risk variables for "Health-Related Quality Of Life (HRQoL)" amid COVID-19 hospital discharged patients. Materials and Techniques: For this cross-sectional study, 1000 discharged patients who tested positive at the tertiary care center before January 2022 were included. The HRQoL was measured using a 5-level EuroQoL survey. The complete health state was evaluated using an Indian value set. The correlation of HRQoL and the clinical, sociodemographic parameters were investigated using appropriate statistical tools. Finally, regression model was utilized to identify all factors that predict the HRQoL dimensions. Results: It was found that 55% of patients said they had moderate or serious health issues. Forty percent of respondents said they had felt moderate-to-severe pain or discomfort, compared to 41% who said they had anxiety or sadness. The outcome of the logistic regression demonstrated the substantial influencers were "age, gender, occupation, location of care, heart conditions, and diabetes" on several HRQoL aspects. Conclusion: The COVID-19 dramatically worsens the patients' physical and mental health conditions. Therefore, the government and policymakers must develop comprehensive ways to lessen the patients' mental and physical health problems.